The Effect Of Service Quality And Company Image On Customer Satisfaction At Sinar Mas Insurance Bengkulu City - Ican Ramadis; Herlina, Yeni; Yanti, Rina Trisna (Utami Publisher, 2025)
The company as an organisation has a goal of making a profit, therefore the company will try to attach importance to customer satisfaction. The purpose of this study was to examine whether there is an effect of service quality and company image on customer satisfaction at Asuransi Sinar Mas Bengkulu City. This company is the largest general insurance company in Indonesia. Based on the characteristics of the study, the research sample was obtained, namely 97 respondents, the method used in collecting data for this study was a questionnaire. The data analysis method in this study is the Multiple Linear Regression Research Instrument Test Hypothesis Determination Coefficient. Based on the results of this study, it is concluded that the service quality variable has an effect on customer satisfaction. The service quality variable (X1), shows t count of 1.722> t table 1.661 with a significant level of 0.008 <0.050. So it can be concluded that the service quality variable has a positive and significant effect on customer satisfaction Asuransi Sinar Mas Bengkulu Branch. This means that the hypothesis is accepted. The company image variable has an effect on customer satisfaction. The company image variable (X2), shows t count of 1.711> t table 1.661 with a significant level of 0.06 <0.050. So it can be concluded that the company image variable has a positive and significant effect on customer satisfaction. This means that the hypothesis is accepted. independent variables, namely the service quality variable (X1) and the corporate image variable (X2) simultaneously affect the dependent variable, namely customer satisfaction (Y). This means that the hypothesis is proven, namely the variables of service quality and company image together or simultaneously have a positive effect on customer satisfaction of Asuransi Sinar Mas Bengkulu Branch.